Allele mining in diverse accessions of tropical grasses to improve forage quality and reduce environmental impact. (28th July 2021) - Hanley, Steve J; Pellny, Till K; de Vega, Jose J; Castiblanco, Valheeria; Arango, Jacobo; Eastmond, Peter J; Heslop-Harrison, J S (Pat); Mitchell, Rowan A C
Abstract: Background and Aims: The C4 Urochloa species (syn. Brachiaria ) and Megathyrsus maximus (syn. Panicum maximum ) are used as pasture for cattle across vast areas in tropical agriculture systems in Africa and South America. A key target for variety improvement is forage quality: enhanced digestibility could decrease the amount of land required per unit production, and enhanced lipid content could decrease methane emissions from cattle. For these traits, loss-of-function (LOF) alleles in known gene targets are predicted to improve them, making a reverse genetics approach of allele mining feasible. We therefore set out to look for such alleles in diverse accessions of Urochloa species and Megathyrsus maximus from the genebank collection held at the CIAT. Methods: We studied allelic diversity of 20 target genes (11 for digestibility, nine for lipid content) in 104 accessions selected to represent genetic diversity and ploidy levels of U. brizantha, U. decumbens, U. humidicola, U. ruziziensis and M. maximum . We used RNA sequencing and then bait capture DNA sequencing to improve gene models in a U. ruziziensis reference genome to assign polymorphisms with high confidence. Key Results: We found 953 non-synonymous polymorphisms across all genes and accessions; within these, we identified seven putative LOF alleles with high confidence, including those in the non-redundant SDP1 and BAHD01 genes present in diploid and tetraploid accessions. These LOF alleles could respectively confer increased lipid content and digestibility if incorporated into a breeding programme. Conclusions: We demonstrated a novel, effective approach to allele discovery in diverse accessions using a draft reference genome from a single species. We used this to find gene variants in a collection of tropical grasses that could help reduce the environmental impact of cattle production.